Implementation of Energy Policy in the European Union Countries in the Aspect of their Sustainable Development. (June 2018) - Kowalik, J; Zawada, M; Szajt, M; Kucęba, R
Abstract: The energy sector in the European Union is currently undergoing very deep transformations from the transition from conventional energy to new technologies and renewable energies. By defining energy policy guidelines, the European Union has followed the principle of sustainable development and has adopted the following targets for the development of the energy sector for the years 2010-2020: 20% reduction of greenhouse gas emissions, 20% increase of renewable energy share in final energy consumption, by 20% and by increasing the share of biofuels in the total consumption of transport fuels by at least 10%. The aim of the article was to analyze the current state of implementation of the basic assumptions of the Community in the field of energy policy. The ambitious energy policy objectives for 2010-2020, as outlined by the European Union, have been demonstrated to a varying extent by the Member States of the Community. This was influenced primarily by the global economic crisis, the diversification of the political and economic interests of individual member states, and the large diversification of strategic energy carriers.